Does Environmental Uncertainty Play Moderating Role in Relation Between Business Strategy and Tax Avoidance - HAMDIAH, Hamdiah; TJAHJONO, Mazda Eko Sri; BASTIAN, Elvin; SOLEHA, Nurhayati (Journal of Governance, Taxation and Auditing, 2024)
This research aims to analyze the effect of implementing a company's business strategy on the level of tax avoidance with environmental Uncertainty as a moderating variable. The population in this research is manufacturing companies on the Indonesia Stock Exchange in 2019-2022. The sampling technique used purposive sampling and obtained 91 companies. This quantitative research uses secondary data in the form of annual reports of manufacturing companies. The model used is panel data regression with a Random Effect (RE) testing model. This research produced three critical findings. First, the prospector strategy has a significant positive effect and is more aggressive in tax avoidance than the defender and analyzer strategies. Second, the defender strategy negatively and less aggressively influences tax avoidance compared to the prospector and analyzer strategies. Third, the relationship between business strategy and tax avoidance is moderated by environmental Uncertainty because it can strengthen the relationship between prospector strategy and tax avoidance and weaken the relationship between defender and analyzer strategies and tax avoidance. (weakening) Moreover, it can positively moderate the relationship between prospector strategy and tax avoidance (strengthening).